(untitled) (Contemporary Mathematics, 2023)
A single server has a limited amount of storage and processing power dependent queueing model with examination of a control strategy, manageable rates of arrival and balking in reverse is examined in this paper. Using this model, a steady-state solution and system characteristics may be found. To aid comprehension, numerical findings are provided, as well as a pertinent conclusion.